The Arab and Islamic Arts’ Pressing References to Abstraction - Najem, Sarmad Mohammed (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The great influence on the cultures of different countries that characterized that stage, because of the Islamic conquests and the adoption of the Islamic faith by many peoples, and their migration to the Islamic cities at that time, accompanied by their art and the methods of its formulation. This brings us to a question about the influential references that call the Arab Muslim artist to opt for the abstract style and adhere to it. This was the problem of the research that was included in the methodological framework, as well as the importance of the research, its aim, its limits, and specifically its terminology. It relied on the indicators of the theoretical framework, which represented the analysis tool, according to which the results of the research were reached and then its conclusions, the most important of which are; (1) The Islamic doctrinal reference was a pressure towards the abstraction style; It is a natural result of the transformation of the Arab from the sensual pagan belief into the spiritual belief of Islam. The expression in the art of what is spiritual - even among non-Muslims, such as African blacks, for example - takes on an abstract character. There was a dislike or prohibition of the simile method; (2) Aesthetic thought is an influential reference, reflected in the artist’s output. Its production was based on Islamic aesthetic values: moderation, consistency, proportionality, and organization, in an unremitting attempt to follow the example of divine perfection, which is the secret of beauty.